A New Take on V(D)J Recombination: Transcription Driven Nuclear and Chromatin Reorganization in Rag-Mediated Cleavage - Chaumeil, Julie; Skok, Jane A. (Frontiers in Immunology, 2013)
It is nearly thirty years since the Alt lab first put forward the accessibility model, which proposes that cleavage of the various loci is controlled by lineage and stage specific factors that regulate RAG access to the different loci. Numerous labs have since demonstrated that locus opening is regulated at multiple levels that include sterile transcription, changes in chromatin packaging and alterations in locus conformation. Here we focus on the interplay between transcription and RAG binding in facilitating targeted cleavage. We discuss the results of recent studies that implicate transcription in regulating nuclear organization and altering the composition of resident nucleosomes to promote regional access to the recombinase machinery. Additionally we include new data that provide insight into the role of the RAG proteins in defining nuclear organization in recombining T cells.